Advocacy for Processing Cassava Noodles Based on High-Protein Local Food as Supplementary Feeding for Toddlers to Support Family Nutrition - Iin Purnamasari; Sugeng Maryanto; Suwarno Widodo; Nur Cholifah; Siska Dea Novitasari; Vanes Ufi Safarah; Novia Eka Rahmawati; Ajeng Ayu Nur Fitriyani; Afim Rofkhul Roim (Warta LPM, 2025)
The purpose of this program is to increase the understanding of mothers under five and posyandu cadres about the benefits of cassava as an alternative source of carbohydrates and to introduce high-protein cassava noodle formulations that can be produced independently at the household level. The object of the activity includes the Team PKK Pokja 4, Posyandu Cadre, and Health cadres in partner villages. In addition, the advocacy for processing cassava noodles based on high-protein local foods was developed as an effort to fulfill the nutritional needs of toddlers through Supplementary Feeding (PMT), which is easily accepted by the community and supports family food security. The methods used include a participatory approach through family nutrition socialization, cassava noodle processing demonstrations, and targeted group discussions to explore community perceptions and needs. Data was collected through observations, brief interviews, and product acceptance assessments. Advocacy is applied by providing training in the processing of cassava noodles with 30% theoretical and 70% practical. Appropriate Technology/TTG is downstreamed to participants in the hope that the knowledge gained can be sustainable. The results of the activity showed that high-protein cassava noodles were well received by mothers under five because they were considered a nutritious dietary supplement variation, easy to make, and used affordable local ingredients. Posyandu cadres also expressed their readiness to integrate this innovation into the routine PMT menu. It is recommended that the production of cassava noodles be facilitated through advanced training, support for simple tools, and collaboration with PKK and local food UMKM to ensure its sustainability. In addition, it is necessary to conduct a more comprehensive nutritional content test and monitoring of the impact on the nutritional status of toddlers to strengthen the scientific basis of the program.